ANALISIS PERANCANGAN SISTEM INFORMASI AKUNTANSI PADA SIKLUS PENGGAJIAN DALAM RANGKA EFEKTIVITAS PENGENDALIAN INTERNAL (STUDI KASUS PADA PERUSAHAAN PLASTIK INJECTION) - DANKE, YUANITA (Berkala Ilmiah Mahasiswa Akuntansi)
The study was conducted on CV MIK engaged in plastic injection. Payroll system by the company is now less effective, so the process of payroll calculation contains many errors. Activity still contain many false payroll is calculated, both in calculating the bonuses given to employees for overtime performed well over the pieces that are charged to the employee, and the reduction of employee loans are charged to the employee's salary. In addition the company still does not have adequate documentation for the provision of information required. The purpose of this research is to design a computerized payroll system that will be expected to help solve problems facing the company. Given these problems, needed repairs and design a better system. Therefore conducted an analysis of company procedures and conducted an evaluation of the analysis has been performed. Evaluation procedures and flowcharts in the study were divided into five events, namely acceptance and placement of employees, time recording, payroll calculation, payroll, and recordkeeping and reporting. With the designed payroll computer-based information systems, errors of calculation of employee salaries that often occur in a manual system can be reduced or even absent and can generate the required information quickly and accurately, and can result in reports that can be useful for decision making for the management company.